Biased attentional processing of positive stimuli in Social Anxiety Disorder: An eye movement study. - Chen, N.; Clarke, Patrick; MacLeod, C.; Guastella, A. (Routledge, 2012)
Despite the established relationship between social anxiety and attentional bias towards threat, a growing base of evidence suggests that social anxiety is additionally maintained by a deficit in the attentional processing of positive information. However, it remains unclear which component of attention is implicated in this deficit. Using eye movement-based measures and a novel attentional cuing methodology, the present study sought to investigate the presence of anxiety-linked bias in attentional engagement with, attentional disengagement from, and total fixation time to, socially relevant emotional stimuli in individuals diagnosed with social anxiety disorder, relative to non-socially anxious controls. Socially anxious individuals were found to exhibit faster attentional disengagement from positive stimuli, and reduced total fixation time to all emotional stimuli, relative to controls. Additionally for socially anxious individuals, lower total fixation times to positive stimuli were associated with higher levels of state anxiety. No differential pattern of engagement was evident between groups. We conclude that social anxiety is maintained in part by the aberrant processing of positive social stimuli.